KEPEMIMPINAN ADAPTIF: KOMPETENSI PEMIMPIN MENGHADAPI PERUBAHAN PADA THE ABUNDANCE ERA - Amal Fathullah; Muhammad Rizki Rezani (Berajah Journal, 2026)
The Society 5.0 era and the Abundance Era bring with them an abundance of information, rapid technological advancement, and disruption that demand leaders possess adaptive and visionary competencies. This study aims to identify the leadership competencies required to navigate change in the Society 5.0 era, as well as to analyse the relevance of the transformational leadership model in responding to the dynamics of technological and information abundance. The research method employed is a literature review, examining various scientific articles, research reports, and academic sources related to leadership, change management, and the development of Society 5.0. The results indicate that leaders in the 5.0 era must master core competencies such as critical thinking, innovation, digital literacy, and the ability to manage change sustainably. Furthermore, the success of transformational leadership is significantly influenced by regulatory support, organisational policies, and the availability of adequate resources. Consequently, today’s leaders need to capitalise on the opportunities presented by technological abundance whilst ensuring the organisation is prepared to undergo strategic transformation.